Beyond the hype: Mobile phones and the web to improve agricultural value chains - Mundy, Paul; Addom, Benjamin K.; Bheenick, Krishan (Technical Centre for Agricultural and Rural Cooperation, 2017)
A smartphone is a wonderful thing. This miniature computer in our pockets is changing the way we live, how we get information and communicate with each other. Each phone comes loaded with “apps” – programs that do specific things, like finding out how much something costs (and buying it), sending photos to friends, finding our way in an unfamiliar town. And if we don’t have the right app, we can easily download one with a couple of taps on the screen. Mobile phones are already surprisingly common in many parts of the developing world, and they, and the network of cables and transmitter masts that are needed to carry all that data, are spreading fast. The service in many places is still patchy and intermittent: people have to climb the nearest hill to get a signal. Many still have basic mobile phones that allow simple text messages and voice calls, rather than the latest smartphone with a colour screen and the latest gizmos. But both mobile phone services and the availability of smartphones are improving, and quickly.